The Wyclif case in late medieval England: an example of the interaction between philosophy, politics, social criticism and language - Fernández, Carolina Julieta (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
At the end of the 14th century, England came to face stages of fiscal suffocation due to the already long Hundred Years’ War with France (dde. 1337); is witness to the violent peasant-urban uprising of 1381 and its even more violent repression, and is moved by Enrique Bolingbroke’s coup against Richard II, within the framework of a dialectic between authority and negotiation between crown and nobility, typical of of the pre-absolutist stage of the European national states. Within this context, a priest and preacher who ranks among the leading philosophers and theologians of the second half of the century at Oxford, Europe’s second leading academic world, John Wyclif (c. 1330-1284), infuses with his fiery preaching a spirit of criticism and reform that marks the social pulse, religiosity, literature and language of subsequent decades. This is what is known as the Lollard movement, which the ecclesiastical establishment of the following decades configured as a heresy that was the object of persecution until almost the middle of the 15th century. Among its main emergents is the so-called Wyclifite Bible (c. 1390-1420), an anonymous corpus of Middle English texts decisive for the establishment and maturation of the modern English language. We are before a rare case of a heresy of university origin; a complex phenomenon, impossible to approach, except through various disciplines: the histories of philosophy, theology and spirituality; the social, economic history and of the national states; the history of language and literature; that of texts, their fixation and transmission. At stake is the relationship between the preachers or "poor priests", the uprising and its program, the program of Wyclif himself, the university students and power (in its double ecclesiastical and secular facet, typically medieval).